2018
DOI: 10.1038/s41591-018-0116-5
|View full text |Cite
|
Sign up to set email alerts
|

Tumor innate immunity primed by specific interferon-stimulated endogenous retroviruses

Abstract: Mesenchymal tumor subpopulations secrete pro-tumorigenic cytokines and promote treatment resistance. This phenomenon has been implicated in chemorefractory small cell lung cancer and resistance to targeted therapies, but remains incompletely defined. Here, we identify a subclass of endogenous retroviruses (ERVs) that engages innate immune signaling in these cells. Stimulated 3 prime antisense retroviral coding sequences (SPARCS) are oriented inversely in 3' untranslated regions of specific genes enriched for r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
206
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 242 publications
(218 citation statements)
references
References 38 publications
10
206
0
2
Order By: Relevance
“…Besides the expression of HERVs induced by DNA methylation inhibitors, some specific genes were identified to be associated with the induction of HERV‐derived dsRNAs. Cañadas et al found that expression of a novel subclass of ERVs was triggered in mesenchymal tumor subpopulations with high AXL/MET expression and low EZH2 levels when exposed to IFN‐γ . Expression of such ERVs promoted MHC class 1 upregulation, T‐cell infiltration, activation of immune checkpoints, and myeloid infiltration, thus promoting tumor immune suppression.…”
Section: Functional Roles Of Hervs In Carcinogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the expression of HERVs induced by DNA methylation inhibitors, some specific genes were identified to be associated with the induction of HERV‐derived dsRNAs. Cañadas et al found that expression of a novel subclass of ERVs was triggered in mesenchymal tumor subpopulations with high AXL/MET expression and low EZH2 levels when exposed to IFN‐γ . Expression of such ERVs promoted MHC class 1 upregulation, T‐cell infiltration, activation of immune checkpoints, and myeloid infiltration, thus promoting tumor immune suppression.…”
Section: Functional Roles Of Hervs In Carcinogenesismentioning
confidence: 99%
“…Cañadas et al found that expression of a novel subclass of ERVs was triggered in mesenchymal tumor subpopulations with high AXL/MET expression and low EZH2 levels when exposed to IFN-γ. 142…”
Section: Regulation Of Innate Immunity By Hervsmentioning
confidence: 99%
“…While these results are not sufficient to conclude that Tbk1 loss promotes antitumor immunity in PDA, the idea is not unreasonable given that Tbk1 Δ/Δ mice have been shown to produce higher levels of pro-inflammatory cytokines in response to immune challenge [12]. In agreement with the notion that Tbk1 loss produces antitumor immunity, two recent studies reported that immune evasion and metastatic behavior are highly associated with the engagement of the cGAS-STING-TBK1 innate immune pathway in cancer cells [50][51][52]. In the first study, Backhoum et al [51] found that chromosomal instability in cancer cells, caused by errors in chromosomal segregation during mitosis, promoted cellular invasion and metastasis through the introduction of double-stranded DNA into the cytosol, engaging the cGAS-STING-TBK1 antiviral pathway.…”
Section: Discussionmentioning
confidence: 95%
“…In the first study, Backhoum et al [51] found that chromosomal instability in cancer cells, caused by errors in chromosomal segregation during mitosis, promoted cellular invasion and metastasis through the introduction of double-stranded DNA into the cytosol, engaging the cGAS-STING-TBK1 antiviral pathway. In the second report, Cañadas et al [52] characterized an interferonstimulated positive feedback loop of antisense endogenous retroviruses (ERVs) present in a number of human cancer cell lines that produced hyperactive innate immune signaling, myeloid cell infiltration, and immune checkpoint activation. Additionally, they discovered that high ERV-expressing cancer cells correlate with an Axl-positive mesenchymal state, which is consistent with our observations [52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation